2021
DOI: 10.1093/mnras/stab1087
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and kinematical analysis of the double-barred galaxy NGC 3504 using ALMA CO (2–1) data

Abstract: We present results obtained from ALMA CO (2–1) data of the double-barred galaxy NGC 3504. With three times higher angular resolution (∼ 0.″8) than previous studies, our observations reveal an inner molecular gas bar, a nuclear ring, and four inner spiral arm-like structures in the central 1 kpc region. Furthermore, the CO emission is clearly aligned with the two dust lanes in the outer bar region, with differences in shape and intensity between them. The total molecular gas mass in the observed region (50″ × 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…We note in passing that observations of external barred spirals oftentimes show evidence for an alignment of the molecular bar (if present) with a stellar bar. Examples are M 83 (Lundgren et al 2004;Hirota et al 2018), M 100 (Sempere & Garcia-Burillo 1997), NGC 4569 (Boone et al 2007), and even doubled-barred spirals such as NGC 3504 (Kuno et al 2000;Wu et al 2021). For the Milky Way, determinations of the bar inclination angle indicate values between 20 • (Queiroz et al 2021) and 45 • (Anders et al 2019), but neither of these angles agrees with the vanishing inclination angle of the feature described above.…”
Section: Resultsmentioning
confidence: 90%
“…We note in passing that observations of external barred spirals oftentimes show evidence for an alignment of the molecular bar (if present) with a stellar bar. Examples are M 83 (Lundgren et al 2004;Hirota et al 2018), M 100 (Sempere & Garcia-Burillo 1997), NGC 4569 (Boone et al 2007), and even doubled-barred spirals such as NGC 3504 (Kuno et al 2000;Wu et al 2021). For the Milky Way, determinations of the bar inclination angle indicate values between 20 • (Queiroz et al 2021) and 45 • (Anders et al 2019), but neither of these angles agrees with the vanishing inclination angle of the feature described above.…”
Section: Resultsmentioning
confidence: 90%
“…This model assumes the gas is flowing along f bar . This expression is similar to Hirota et al (2009) and Wu et al (2021), assuming that the gas flows parallel to the bar major axis.…”
Section: Kinematic Interpretation Of the Oval Distortionmentioning
confidence: 81%
“…We showed that this is achieved just by fixing the orientation of the stream flow to the bar major axis in the models, and the radial profiles of the noncircular velocities are consistent with the residuals from circular rotation, with possible differences in amplitudes due to assymmetric drift and other random motions not considered in the model as we showed in Figure 7. Apart from the elliptical motions considered in the bisymmetric models, radial inflows are expected in bars, and these are observed to occur along the bardust lanes (Wu et al 2021;Sormani et al 2023). Our implementation of an inflow model is therefore physically motivated.…”
Section: Discussionmentioning
confidence: 99%
“…Our proposed scenarios in association with the models by Sormani et al (2019Sormani et al ( , 2020 and (Tress et al 2020) can be supported by observations of galactic centres in other galaxies. Equivalents of the near and far side dust lanes, attributed to the Milky Way's CMZ, have been observed in, for example the centres of M 83 (Harada et al 2019;Callanan et al 2021), NGC 3504 (Wu et al 2021), and, recently, in a couple of more nearby galaxies thanks to the high angular resolution of the PHANGS survey (Physics at High Angular resolution in Nearby GalaxieS, e.g. Lee et al 2022).…”
Section: Implications For the Cmzmentioning
confidence: 99%